Change in unit‐level job attitudes following strategic interventions: A meta‐analysis of longitudinal studies. (14th May 2021) - Solinger, Omar N.; Joireman, Jeff; Vantilborgh, Tim; Balliet, Daniel P.
Summary: The present meta‐analysis tests how cost‐ and people‐oriented strategic interventions impact temporal‐dynamic changes in unit‐level job attitudes within organizations. Analyses are based on 573 effect sizes across 137 longitudinal studies containing unit‐level change in job attitudes across three time periods (pre‐change, during change, and post‐change). Results reveal that unit‐level job attitudes (a) decline during cost‐oriented changes (e.g., restructuring) and remain at lower levels following the changes (supporting a sustained change model); (b) increase during people‐oriented changes (i.e., HRM investments) and remain at higher levels following the interventions (consistent with a sustained change model); and (c) remain unchanged over time when cost‐ and people‐oriented interventions are combined. Tests of a process model further reveal that cost‐oriented (people‐oriented) interventions impact unit‐level job attitudes by reducing (increasing) perceived support (relative to a no intervention control). The pattern of findings suggests that long‐term, unit‐level change in job attitudes can be anticipated to follow from strategic interventions, although some of the negative impact of cost cutting can be mitigated by maintaining perceptions of support.